2018
DOI: 10.1016/j.jid.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Time Effects on NB-UVB–Induced Erythema in Human Skin In Vivo

Abstract: Similar itch and nociceptive sensations evoked by punctate cutaneous application of capsa-icin, histamine and cowhage. Pain 2009;144: 66e75.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Chronic exposure to UVB irradiation injures skin, causing premature wrinkles, dryness, thinning, and increased pigmentation [6,17,18], as well as acute inflammation such as edema and erythema [19][20][21][22]. Most of these phenomena occur due to damage to the dermis, where fibroblast cells are located.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to UVB irradiation injures skin, causing premature wrinkles, dryness, thinning, and increased pigmentation [6,17,18], as well as acute inflammation such as edema and erythema [19][20][21][22]. Most of these phenomena occur due to damage to the dermis, where fibroblast cells are located.…”
Section: Introductionmentioning
confidence: 99%
“…For example, p53 activity is controlled by BMAL1 in pancreatic cancer 30 , and p53 negatively regulates Per2 expression 22 . Another group demonstrated that UV triggers time-dependent erythemal responses in human skin cells through CRY2 and p53 31 , 32 . These observations imply that the molecular clock responds to genotoxic stress by resetting its phases and simultaneously regulating stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian clock proteins and genes have been shown to regulate cellular responses after UVB exposure: in mice, sensitivity to UVB‐induced DNA damage in the epidermal skin is a process that is dependent on ARNTL as a function of the time of day . Earlier, we showed the effect on circadian timing in UVB‐induced erythema response in human epidermal/dermal skin . However, the effect of UVB radiation on clock genes is not fully understood.…”
Section: Introductionmentioning
confidence: 98%